2016
DOI: 10.1104/pp.16.00476
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Basis of Stomatal Density and Flux  

Abstract: Since the first published measurements of stomatal density by Johann Hedwig (1793) and Alexander von Humboldt (1798), the counting and measuring of stomata has been one of the most typical botanical activities, with an important role across fields of plant biology (Willmer and Fricker, 1996). Stomatal density (d) and size (s) are indicators of acclimation and adaptation to contrasting environments, and permit estimation of the theoretical anatomical maximum stomatal conductance (g max ; units: mol m 22 s 21

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 45 publications
(54 reference statements)
6
107
0
Order By: Relevance
“…By understanding the adaptive significance of leaf anatomical variation we can learn about natural history, find targets for crop improvement and identify anatomical proxies for paleoclimates preserved in the fossil record (Wolfe, ; Royer, ; McElwain & Steinthorsdottir, ). The size, density and distribution of stomata on a leaf vary widely and impact the flux of CO 2 and water vapor (recently reviewed in Sack & Buckley, ), as well as susceptibility to foliar pathogens that infect through stomata (McKown et al ., ; Melotto et al ., ). Hence, stomata have been especially useful in understanding plastic and evolutionary responses to climate change and domestication (Woodward, ; Beerling & Royer, ; Milla et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By understanding the adaptive significance of leaf anatomical variation we can learn about natural history, find targets for crop improvement and identify anatomical proxies for paleoclimates preserved in the fossil record (Wolfe, ; Royer, ; McElwain & Steinthorsdottir, ). The size, density and distribution of stomata on a leaf vary widely and impact the flux of CO 2 and water vapor (recently reviewed in Sack & Buckley, ), as well as susceptibility to foliar pathogens that infect through stomata (McKown et al ., ; Melotto et al ., ). Hence, stomata have been especially useful in understanding plastic and evolutionary responses to climate change and domestication (Woodward, ; Beerling & Royer, ; Milla et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the density and size of stomata have been researched extensively (Sack & Buckley, , and references therein), the adaptive significance of stomatal distribution is less well understood. Stomata are most often found only on the lower leaf surface (hypostomy), but occur on both surfaces (amphistomy) in many species (Metcalfe & Chalk, ; Parkhurst, ; Mott et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study of 90 species of woody and semi-woody plants showed that f ranged from 2.8% to 33% (Cornelissen et al, 2003), and our study extended the range of f from 0.20% to 40.5%. This 200-fold variation in f across species would have strong functional consequences, as f reflects variation in stomatal pore index (across our species, SPI was tightly correlated with f; R 2 = 0.94, p < .001; Figure S3a), and in the anatomical maximum stomatal conductance (Sack & Buckley, 2016; R 2 = 0.43, p < .001; Figure S3b).…”
Section: Variation In Leaf Stomatal Traitsmentioning
confidence: 93%
“…Stomatal measurements were obtained from microscopy images taken from nail varnish impressions of both leaf surfaces. We measured stomatal density ( d ) and stomatal index (i.e., differentiation rate, the number of stomata per numbers of stomata plus epidermal pavement cells, i ), stomatal pore length (SP L ), guard cell length and width (GC L , GC W ), stomatal area ( s ) and epidermal pavement cell area ( e ) (Sack, Melcher, Liu, Middleton, & Pardee, ) and calculated the maximum theoretical stomatal conductance ( g max ; Franks & Farquhar, ; Sack & Buckley, ).…”
Section: Methodsmentioning
confidence: 99%
“…Fourth, we hypothesized that across species, RGR and m would be positively correlated due to life-history trade-offs, and parallel associations with given traits (Kitajima, 1994;Philipson et al, 2014;Russo et al, 2010;Visser et al, 2016;Wright et al, 2010). Further, we hypothesized that RGR and m would relate positively to photosynthetic rate (Donovan & Ehleringer, 1994;); leaf area (Iida et al, 2016), N and P concentrations (Iida et al, 2016;Osone, Ishida, & Tateno, 2008); the sizes and numbers of stomata (Hetherington & Woodward, 2003;Wang et al, 2015); maximum stomatal conductance and vein densities (Hetherington & Woodward, 2003;Iida et al, 2016), and negatively to LMA (…”
Section: Introductionmentioning
confidence: 99%